2011
DOI: 10.1093/cid/cir232
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Incidence and Case Fatality Rates From Hemorrhagic Fever With Renal Syndrome in China, 2004–2008

Abstract: These data illustrate a paradox in which the incidence of disease is greater for males, but the severity of disease outcome is worse for females. Several behavioral, societal, and biological factors are hypothesized to be involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
60
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 26 publications
7
60
3
Order By: Relevance
“…In Sweden and Finland, gender-specific differences in symptoms as well as mortality rates were identified for epidemic nephropathy [27,28]. A similar observation was reported for HFRS in China [29]. Our results showed no association between gender and severity of disease (p = 0.945), which is similar to results reported in German patients [30].…”
Section: Discussionsupporting
confidence: 90%
“…In Sweden and Finland, gender-specific differences in symptoms as well as mortality rates were identified for epidemic nephropathy [27,28]. A similar observation was reported for HFRS in China [29]. Our results showed no association between gender and severity of disease (p = 0.945), which is similar to results reported in German patients [30].…”
Section: Discussionsupporting
confidence: 90%
“…A similar pattern is found in cancer research, where male research subjects dominate the trials 11 , or in studies of cell tissue and laboratory animals, where the sex of the subject often goes unrecorded 12,13 . Even in research involving both sexes, data is often not analysed by sex, and results may therefore not be accurate for either male or female subjects 14 . Both women and men face disadvantages under these circumstances.…”
mentioning
confidence: 99%
“…Although some risk factors are known, for example, age, sex, and living in a rural region (4,26,27), evidence is conflicting (28,29). Some studies have shown that seropositivity is significantly higher in men than in woman, and some have reported sex as a risk factor for Hantavirus infection (7,29,31). In one retrospective study, which investigated the clinical signs of 75 patients with Hantavirus infection aged 16-82 years, the infection rate was 2.5 times higher in men than in women (10).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, other studies have shown no association between sex and frequency of Hantavirus infection (27,30). There is also a lack of consensus regarding the etiology of this sex imbalance, although some hypotheses suggest hormonal, behavioral, immunologic, or genetic factors (31).…”
Section: Discussionmentioning
confidence: 99%